2018
DOI: 10.1159/000489593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CXCR4 on Apoptosis in Osteosarcoma Cells via the PI3K/Akt/NF-κβ Signaling Pathway

Abstract: Background/Aims: Osteosarcoma, the most common primary bone malignancy, arises from primitive transformed cells of mesenchymal origin with the worldwide increasing morbidity and mortality. Previous studies found apoptosis of osteosarcoma cells was essential for an effective manner to improve the progress of osteosarcoma, and CXCR4 has been demonstrated to be relevant with various tumor progress and metastasis. Methods: The proliferation of cells transfected with CXCR4 shRNA and control shRNA were measured by B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…[ 33 ] Previous study also found that CXCL12/CXCR4 is critical for cell proliferation via activation of ERK signaling pathway, [ 34 ] and there is also study indicated that down-regulation of CXCR4 reduce the proliferation of cancer cells via inhibition of NF-κB signaling pathway with induction of cellular apoptosis. [ 35 ] Thus, we speculated that cetuximab targeted on Ras/Raf/MAPK signaling pathway, leading to the reduction in signaling pathway activation. Besides, we found that inhibition of ITGB1 targets on CXCL12/CXCR4, the upstream molecular of Ras/Raf/MAPK signaling pathway, resulting in reduction of cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] Previous study also found that CXCL12/CXCR4 is critical for cell proliferation via activation of ERK signaling pathway, [ 34 ] and there is also study indicated that down-regulation of CXCR4 reduce the proliferation of cancer cells via inhibition of NF-κB signaling pathway with induction of cellular apoptosis. [ 35 ] Thus, we speculated that cetuximab targeted on Ras/Raf/MAPK signaling pathway, leading to the reduction in signaling pathway activation. Besides, we found that inhibition of ITGB1 targets on CXCL12/CXCR4, the upstream molecular of Ras/Raf/MAPK signaling pathway, resulting in reduction of cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In K562 shFtH cells, CXCR4 up-regulation promotes the nuclear translocation of p65 subunit belonging to the transcriptional complex NF-κB. There is increasing evidence suggesting a reciprocal interplay between CXCR4 and NF-κB signaling in fine tuning cancer cellular signaling pathways (23,24). Although the vast majority of data report that NF-κB contributes to the increase in CXCR4 expression (64), few recent reports suggest the possible existence of a regulatory feedback loop (24).…”
Section: Discussionmentioning
confidence: 99%
“…In chronic myelogenous leukemia (CML) cells, CXCR4 activates PI3K/AKT signaling pathway and promotes the translocation of NF-κB complexes into nucleus thereby decreasing the expression of pro-apoptotic proteins (23,24). Moreover, CXCL12 activates pro-survival signal pathways including those mediated by MAPK, S-6-kinase, STAT3 and STAT5, and in vitro treatment with CXCR4 antagonists inhibits cell growth and induces cell death (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…8 Interaction of CXCR4 and CXCL12 activates intracellular signals, such as JAK2/STAT3, MEK/ERK and PI3K/AKT pathway to promote cell proliferation, migration, and survival. Jiang et al 23 reported that CXCR4 downregulation induces osteosarcoma cells apoptosis through inhibition of PI3K/AKT/NF-kB pathway. PI3K/AKT pathway is an intracellular signaling pathway which involves in DLBCL lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%